Design, analysis and fabrication of ice cream machine with dispenser / Nur’ain Humaira Mohamad Nasir and Nurulsaidatulsyida Sulong - Mohamad Nasir, Nur’ain Humaira; Sulong, Nurulsaidatulsyida (School of Mechanical Engineering, 2022)
During this globalisation era, many machines and electrical devices have been created or upgraded into a better version to make people feel more comfortable and ease their work. An ice cream machine with a dispenser is developed according to the market demand. Due to difficulties in freezing the ice cream and storing the toppings, this project aims to fabricate an ice cream machine with a dispenser that can freeze the ice cream less than overnight by using Peltier as a cooling element. The cooling element is powered by power supply AC to DC because it is more efficient and easier. This project is to design, analyse, and fabricate an ice cream machine with a dispenser that can save more time and easy to dispense the toppings. To conclude, this machine will give benefits to many people